A Novel Coverage Enhancement Algorithm for Image Sensor Networks. (27th May 2012) - Huang, Haiping; Sun, Lijuan; Wang, Ruchuan; Li, Jing
Abstract : The needs of diverse environmental information introduce the multimedia data into wireless sensor networks. The characteristics of most multimedia information, such as great amounts of data and high-quality requirement for network service, positively affect traditional wireless sensor networks, which also derive various new research areas. This paper focuses on the multimedia image sensor networks and proposes FVPTR (fuzzy image recognition and virtual-potential-field-based paired tangent point repulsion) method to enhance the perspective coverage of network. This approach utilizes fuzzy image recognition method to process the boundary nodes. Aimed at nonboundary nodes, based on potential field theory, it adopts paired tangent point repulsion mechanism, which attempts to obtain the optimal network sensing coverage through the multiple paired achievements between one current node and several target nodes. Combined with FVPTR, some algorithms such as LRBA, MBAA, and mixed superposition algorithm are put forward to single or multiple-time adjustment by the rotation of the direction angle. The results of simulation and all kinds of comparisons show that three-times pairing method enhances the coverage of networks well.